Perlindungan Hukum Bagi Badan Hukum Dalam Proses Online Single Submission (Oss) Terhadap Syarat Operasional Badan Hukum - Tarida Sondang; Wira Franciska; Doni Martien (Syntax Idea)
A Limited Liability Company is a legal entity which is expressly recognized by law as a legal entity which is a legal subject. The main need for an authentic deed in the business sector is the deed of a limited liability company (PT) legal entity. This study aims to analyze and understand the policies related to obtaining business licenses for limited liability companies in the online single submission system in Indonesia and legal protection for limited liability companies in obtaining business licenses through online single submission in accordance with applicable laws and regulations. The method used in this research is normative juridical research. The data used is secondary data consisting of primary legal materials, secondary legal materials and tertiary legal materials. Besides that, primary data is also used as a support for secondary data legal material data. By using the theory of legal protection and the theory of legal certainty. From the results of the research that PP Number 24 of 2018 concerning electronically integrated business licensing services, namely weak laws and regulations do not regulate legal protection for business actors who do not make adjustments to OSS. Legal protection for Limited Liability Companies in the form of adjustments in implementing the OSS system, namely regarding changes to the Standard Classification of Indonesian Business Fields for Limited Liability Companies that already have and obtain a legal certificate of detention of a business entity issued by the Ministry of Law and Human Rights. Based on the research results, it can be interpreted that First, PTs that do not make adjustments to business licenses through OSS after the issuance of PP Number 24 of 2018, namely weak laws and regulations do not regulate legal protection for business actors who do not make adjustments